Improving the Performance of Conventional Wastewater Treatment Plants - Hadi Ghawi, Ali; Naji Abudi, Zaidun (Iraqi Journal of Civil Engineering, 2012)
Secondary clarifiers form a crucial component in gravity separation processes mainly in solid-liquid separation. They perform the crucial process of separating the activated sludge from the clarified effluent and also to concentrate the settled sludge. As treatment plants receive increasingly high wastewater flow, conventional sedimentation tanks suffer from overloading problems which result in poor performance. Inlet baffle modification by using an energy dissipating inlet (EDI) was proposed to enhance the performance in the circular clarifiers in Al-Dewanyia wastewater treatment plant. A 3-Dimensional fully mass conservative clarifier model was applied to evaluate proposed tank modification and to estimate the maximum capacity of the existing and modified clarifiers. A Computational Fluid Dynamics (CFD) model was formulated to describe tank performance and design parameters were obtained based on the experimental results. The study revealed that velocity and SS are better parameters than TS, BOD5, and COD to evaluate the performance of sedimentation tanks. Removal efficiencies of suspended solids, biochemical oxygen demand, and chemical oxygen demand were higher in the EDI (Baffle).